Listening Deeply : An Approach to Understanding and Consulting in Organizational Culture, Second Edition - Stein, Howard F. (Book collections on Project MUSE., 2017)
Listening deeply is the foundation of all effective organizational management, research, and consulting. This book explores the many aspects of attentive listening through storytelling and includes examples of organizational case studies. In Stein's practice, listening deeply is an attitude evoked by the psychoanalytic concept of hovering attention--a careful attending to the person or group one is trying to help and an equally careful attending to how one is hearing these others. The listener's own feelings are as crucially diagnostic as what the consultant observes in other people. This new edition of Listening Deeply updates historical context, theory, method, and organizational stories. A psychodynamic orientation informs much of the book and the language Stein uses is direct. His lessons are useful to the manager in any kind of organization, as well as practitioners of psychology, sociology, business management, medicine, and education.